Ultrasound and elastography role in pre- and post-operative evaluation of median neuropathy in patients with carpal tunnel syndrome - Wu, Han; Zhao, Hong-Juan; Xue, Wei-Li; Wang, Yi-Chun; Zhang, Wu-Yue; Wang, Xiao-Lei (Frontiers in Neurology, 2022)
Objectives: To investigate the value of conventional ultrasound and real-time shear wave elastography（SWE）in evaluation of median neuropathy in patients with carpal tunnel syndrome (CTS) before and after surgery. Methods: Electromyography examination of 54 wrists of 30 CTS patients and 50 wrists of 25 healthy volunteers was the subject of the study. First, the Boston Carpal Tunnel Questionnaire (BCTQ) was administered to patients with CTS. All subjects were measured at three levels: distal 1/3 of the forearm, carpal tunnel inlet, and distal carpal tunnel using conventional ultrasound and SWE. Median nerve parameters were examined in patients with CTS one week after surgery. Results: The cross sectional area (CSA) and stiffness of the median nerve at the carpal tunnel inlet and distal carpal tunnel were significantly higher in CTS patients than healthy controls (p < 0.001). The CSA and stiffness of the median nerve at the carpal tunnel inlet were statistically significant difference between preoperative and postoperative CTS patients (p < 0.001). The CSA and stiffness of the nerve in CTS patients had a positive correlation to electrophysiology severity. Conclusions: Conventional ultrasound and elastography are valuable in the diagnosis of CTS and are useful in the clinical assessment of patient’s nerve recovery after operation.